2019
DOI: 10.1038/s41396-019-0396-x
|View full text |Cite
|
Sign up to set email alerts
|

Forfeiting the priority effect: turnover defines biofilm community succession

Abstract: Microbial community succession is a fundamental process that affects underlying functions of almost all ecosystems; yet the roles and fates of the most abundant colonizers are often poorly understood. Does early abundance spur long term persistence? How do deterministic and stochastic processes influence the ecological contribution of colonizers? We performed a succession experiment within a hypersaline ecosystem to investigate how different processes contributed to the turnover of founder species. Bacterial a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
63
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 56 publications
10
63
0
Order By: Relevance
“…Our results indicated that the differential action of ecological processes may promote different biogeographic patterns in prokaryotic and picoeukaryotic assemblages in the upper global-ocean. This is consistent with other works using similar approaches to ours indicating that protistan and bacterial assemblages are shaped by different ecological processes [39,[43][44][45]. In particular, selection, which is known to have an important role in structuring prokaryotic communities [27,28], explained a higher proportion of community turnover in surface-ocean prokaryotes (≈ 34-27% of the turnover) than in picoeukaryotes (≈ 17-11%).…”
Section: Discussionsupporting
confidence: 92%
“…Our results indicated that the differential action of ecological processes may promote different biogeographic patterns in prokaryotic and picoeukaryotic assemblages in the upper global-ocean. This is consistent with other works using similar approaches to ours indicating that protistan and bacterial assemblages are shaped by different ecological processes [39,[43][44][45]. In particular, selection, which is known to have an important role in structuring prokaryotic communities [27,28], explained a higher proportion of community turnover in surface-ocean prokaryotes (≈ 34-27% of the turnover) than in picoeukaryotes (≈ 17-11%).…”
Section: Discussionsupporting
confidence: 92%
“…Our results indicated that the differential action of ecological processes may promote different biogeographic patterns in prokaryotic and picoeukaryotic assemblages in the upper global-ocean. This is consistent with other works using similar approaches to ours indicating that protistan and bacterial assemblages are shaped by different ecological processes [37,[41][42][43]. In particular, selection, which is known to have an important role in structuring prokaryotic communities [25,26], explained a higher proportion of community turnover in surface-ocean prokaryotes (~34-27% of the turnover) than in picoeukaryotes (~17-11%).…”
Section: Discussionsupporting
confidence: 92%
“…Prior to oviposition, eggs are coated in a diverse consortium of microbes as they pass through the hen reproductive tract as well as the distal digestive tract (cloaca) [24]. Microbial succession within complex biofilms suggests that founder microbial species play an important role by modifying the local environment in a way that mediates filtering of further microbial inputs later in the successional process [25]. The maternal microbiota deposited on the eggshell could be a potential source of important founder species, setting the stage for a healthy GIT microbiota.…”
Section: Introductionmentioning
confidence: 99%